Hérésies populaires et diabolisation : dissidence, persécutions et réhabilitation des beatas de la Couronne de Castille (1480-1580) - Laurey Braguier (Les Cahiers de Framespa)
This article explores the heresy charges levelled against beatas in Inquisition trials from the late 15th century to the early 17th century. Focusing on trials against these notorious lay communities, this work is designed as a complement to the French and Spanish literature, which has so far looked at the beatas mostly within the broader context of the repression against the Illuminationist sects. First, quantitative elements regarding the beatas are provided, as well as the profiles of key beatas. Then, an analysis is offered of the previously unexplored trials of Mencia Suarez (1487-1490) and Juana de Ribera (1551-1559). Alongside other better-known 16th-century trials, they illustrate both the sketchiness of the charges levelled against them and a diffuse form of heterodoxy, which is very different from that of the early alumbrados movements.